2019
DOI: 10.1111/jbi.13607
|View full text |Cite
|
Sign up to set email alerts
|

The flickering connectivity system of the north Andean páramos

Abstract: Aim To quantify the effect of Pleistocene climate fluctuations on habitat connectivity across páramos in the Northern Andes. Location Northern Andes. Methods The unique páramos habitat underwent dynamic shifts in elevation in response to changing climate conditions during the Pleistocene. The lower boundary of the páramos is defined by the upper forest line, which is known to be highly responsive to temperature. Here, we reconstruct the extent and connectivity of páramos over the last 1 million years (Myr) by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
166
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(182 citation statements)
references
References 101 publications
(112 reference statements)
6
166
0
10
Order By: Relevance
“…Islands may also serve as refugia during periods of climatic change, as in the case of conifers in New Caledonia, which originally derived from the Australian mainland (Condamine, Leslie, & Antonelli, ). Likewise, during ice ages local populations may persist on nunataks (exposed peaks otherwise surrounded by a glacier or snow), recolonizing downhill when the surrounding environment subsequently warms (Flantua & Hooghiemstra, ; Flantua et al, ; Flantua, O'Dea, Onstein, Giraldo, & Hooghiemstra, ; Parducci et al, ).…”
Section: Why Are There So Many Species On Mountains?mentioning
confidence: 99%
See 1 more Smart Citation
“…Islands may also serve as refugia during periods of climatic change, as in the case of conifers in New Caledonia, which originally derived from the Australian mainland (Condamine, Leslie, & Antonelli, ). Likewise, during ice ages local populations may persist on nunataks (exposed peaks otherwise surrounded by a glacier or snow), recolonizing downhill when the surrounding environment subsequently warms (Flantua & Hooghiemstra, ; Flantua et al, ; Flantua, O'Dea, Onstein, Giraldo, & Hooghiemstra, ; Parducci et al, ).…”
Section: Why Are There So Many Species On Mountains?mentioning
confidence: 99%
“…Likewise, during ice ages local populations may persist on nunataks (exposed peaks otherwise surrounded by a glacier or snow), recolonizing downhill when the surrounding environment subsequently warms (Flantua & Hooghiemstra, 2018;Flantua et al, 2014;Flantua, O'Dea, Onstein, Giraldo, & Hooghiemstra, 2019;Parducci et al, 2012).…”
Section: Mountains As Reservoirsmentioning
confidence: 99%
“…Additionally, a widespread species appears to be present in northern páramo sites, and some sister species sympatry may indicate other diversification processes have operated on certain lineages of Panabachia. Divergence time estimates suggest that Panabachia originated in the Miocene, but most species analyzed diverged during the Pliocene and Pleistocene (5.3-0.11 Mya), contemporaneous with the evolution of páramo plant species.Insects 2020, 11, 64 2 of 19 allowing species to exchange genetic material between populations that were usually separated by elevation [5,14], or, alternately, driving the fragmentation of species distributions [5,13,15,16].In the present day, a tropical alpine ecosystem known as páramo is found in the northern Andes above 2800 m, comprising numerous isolated island patches [17,18]. Multiple factors, including isolation due to elevation and climatic oscillations, have played into shaping the current diversity in the páramo [9,18].…”
mentioning
confidence: 99%
“…These include morphological, physiological and behavioral adaptations as results of experiencing harsh abiotic conditions, such as extreme temperatures, higher solar radiation, desiccation and reduced oxygen pressure [19][20][21].The phylogeographic structure of few Andean species has been assessed, most focusing on vascular plants and vertebrate species in a larger phylogeographical context [9,15,22,23]. These studies have revealed that most páramo lineages are quite young (0.0025-5.33 Mya-Pliocene and Pleistocene; [5]), and that the orogeny of the Andes has played an important role shaping their phylogeographical patterns [5,15,[21][22][23]. The few studies done on insect lineages from high elevations have also shown that allopatric speciation is a contributing factor to their diversity patterns [24][25][26][27][28].…”
mentioning
confidence: 99%
See 1 more Smart Citation